236 UTILIZING PAIRWISE COMPARISONS TO DETERMINE RELATIVE IMPORTANCE OF DIABETES GUIDELINES: A COMPARISON OF PHYSICIAN AND PATIENT PERSPECTIVES. (1st January 2005) - Long, M. D.; Centor, R.
Abstract : Objective: Experts and physicians continue to debate quality of care assessment. All parties would like clear accepted guidelines for quality assessment. Most current "report cards" take several measurable quality indicators and average physician performance to provide a single overall score. We asked 3 physician groups and 1 patient group to use the pairwise comparison technique from the analytic hierarchy process (AHP) to evaluate the relative importance of four commonly used diabetes quality indicators. We postulated that both physicians and patients would value indicators differently. This technique allows us to develop a weighted scoring system of overall quality. We also postulated that patients would weight quality indicators differently than physicians. Research Design and Methods: We developed an AHP model to compare four indicators of type II diabetes management: measuring HbA1C, measuring LDL, performance of dilated eye examination and performance of foot examination. Four groups completed pairwise comparisons of these guidelines: academic physicians, community physicians, endocrinologists, and type II diabetic patients. Each subject performed the pairwise comparisons on a Web-based model with either oral or written instructions from a moderator. Results: The table gives the relative weighting for each group. Each row adds to 1.00. Conclusions: All three physician groups had similar rankings of the 4 indicators. Consistently, physicians ranked HbA1C as most important, followed by LDL, eye examination, and foot examination. The patients in this study weighted eye examinations as the second most important indicator, delegating LDL to third. There are several possible explanations for these results. First, patients' value eyesight as a most important component of quality of life. Second, physicians caring for these patients may not emphasize the importance of lipid control. When evaluating overall quality of care which physicians provide, weighting may alter results. Physicians should receive a detailed report card which includes both physician and patient weighting.